Fabrication of Epoxide Functional Hydrophobic Composite Polymer Particles by Suspension Polymerization and Subsequent Doping with Fe3O4 Nanoparticles (Journal of Scientific Research, 2017)
This investigation described a simple three-step process for the fabrication of micrometer-sized magnetic composite polymer particles. This composite polymer particle consisted of crosslinked hydrophobic poly(lauryl methacrylate-divinyl benzene) (P(LMA-DVB)) core, prepared by suspension polymerization. Then, P(LMA-DVB) copolymer core particles were coated with poly(glycidyl methacrylate) (PGMA) by seeded polymerization to introduce epoxide functionality. Finally, P(LMA-DVB)/PGMA composite particles were doped with iron oxide (Fe3O4) nanoparticles following in situ co-precipitation of Fe2+ and Fe3+ from their alkali aqueous solution. The presence of strained oxirane ring derived from PGMA segment present at the surface is expected to induce high affinity towards precipitated magnetic Fe3O4 nanoparticles. The compositional structure of P(LMA-DVB)/PGMA/Fe3O4 composite polymer particles was confirmed by Fourier Transform IR (FTIR), electron microscopy, thermogravimetry (TG), X-ray diffraction (XRD) and energy-dispersive X-ray (EDX).